2007
DOI: 10.1016/j.acn.2007.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological assessment of persons with physical disability, visual impairment or blindness, and hearing impairment or deafness

Abstract: Conducting assessment with individuals with physical disability, visual impairment or blindness, and hearing impairment or deafness poses significant challenges for the neuropsychologist. Although standards for psychological testing have been devised to address assessment of persons with disabilities, little research has been conducted to validate neuropsychological test accommodation and modification practices that deviate from standard test administration or to develop test parameters and interpretive guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 67 publications
0
83
0
1
Order By: Relevance
“…Furthermore, other authors have also found changes in subjects' spatial and temporal senses and their relation with objects after vision loss. [23][24][25][26] In terms of the adjustment process, our sample also focused on different themes of the recovery process in comparison with the older adults previously studied. Most of rehabilitation goals were not only focused on recovery of basic skills and autonomy, but also on the acquisition of new skills to allow a return to work and to realize new projects for future life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other authors have also found changes in subjects' spatial and temporal senses and their relation with objects after vision loss. [23][24][25][26] In terms of the adjustment process, our sample also focused on different themes of the recovery process in comparison with the older adults previously studied. Most of rehabilitation goals were not only focused on recovery of basic skills and autonomy, but also on the acquisition of new skills to allow a return to work and to realize new projects for future life.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge of assessing neuropsychological functioning using tests requiring the use of upper extremities in persons with paralyzed limbs has been reported in the literature 59 . However, non-significant results were still seen when excluding patients with upper limb limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Quadriplegic participants were instructed to use their best grip to hold pens (digit symbol and trail making test) or pins (grooved pegboard) where applicable. However, some participants were not able to complete testing because of the severity of their disability, a problem identified in the literature 59 .…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, we performed standard diagnostic neurocognitive testing in a cross-sectional cohort of 28 children and adults with WAGR syndrome and observed that BDNF haploinsufficiency was associated with lower adaptive behaviour and cognitive functioning, even after accounting for visual impairment, which can be an important confounding factor (Hill-Briggs et al, 2007). While previous case series have described cognitive impairment in individuals with BDNF haploinsufficiency, our study is the first to compare subjects having 11p13 deletions, with and without BDNF involvement, using a systematic diagnostic approach to correlate genotype with neurocognitive phenotype.…”
Section: Discussionmentioning
confidence: 99%